(untitled) (PUBMET, 2023)
The economy of open access (OA) publishing has been a topic of intensive research over the last two decades. Dichotomies between the so-called ’green’ and ’gold’ models, or between fee-based and non-fee-based gold models, the latter known as the diamond model, have been addressed from diverse perspectives. However, some critical insights that would enable a thorough understanding of publishers’ and editors’ decision-making and provide a foundation for developing future evidence-based public policies are still missing. In recent years, more importance has been given to the diamond OA model, and the European research area has recognized its potential to bring change and possibly transform the scholarly publishing landscape. The 2021 EC-funded OA Diamond Journals Study (Bosman et al., 2021) reveals that while Europe is rich in OA Diamond journals, they are far from all being included in the DOAJ, nor are they equally distributed across scholarly disciplines and European regions. The study indicates the dominance of large commercial and APC-based publishers in Western Europe contrasted to the prevalence of smaller, diamond OA publishers in Central and Eastern Europe. Yet, subsequent research by Laakso and Multas (2023) shows that such a distribution across European regions could oversimplify a more diverse landscape. Their bibliometric-based analysis indicates that within regions, countries can vary significantly in their publishing ecosystems, based on several factors: the type (and size) of dominant publishers, the availability of country-level public funding mechanisms for scholarly journals, and the availability of common publishing infrastructures. There are examples of countries from different European regions that appear to be successful in building a thriving and sustainable national diamond publishing ecosystem. However, some publishers adopt an APC-based business model even in such predominantly diamond ecosystems. Our study will be twofold: a comparative investigation will establish the share of APC journals in several dominantly diamond countries: Croatia, Finland, France, Norway, Serbia, and Spain. Although limited in geographical scope, the intended sample will strive for complete coverage of OA journals: authors from each country will provide comprehensive national addenda to DOAJ lists. The publicly available information on the websites of all identified OA journals issued by the publishers located in the countries mentioned above will be inspected for evidence of APC schemes (any fees or charges required of authors or their institutions for submitting or publishing a paper in a journal). The study will address the following research questions: 1. What is the share of journals charging APCs at the time of research (among all OA journals in the country, and especially among journals receiving public subsidies, if there are such subsidies available)?; 2. What is the range, median and mode of APC costs?; 3. Is the existence of APCs and their cost related to the type of a journal publisher or owner, the scholarly discipline, or the fact that the journal is indexed in established international indices and databases? The insight into the incidence of APC-based journals and the context in which they are introduced will be complemented with a qualitative analysis of APC descriptions. This is expected to reveal some of the reasons for their introduction and possibly show that smaller publishers could resort to some local and nonstandard mechanisms. It will answer additional research questions: 4. Are there any specificities of the APC mechanisms among the analysed journals (waivers, discounts, membership fees, etc.)?, and 5. How transparent are journals about their APCs? (What are the terms used for APCs in different languages? Are they listed in their DOAJ records? Is it explained what they are charged for and how the funds are used?). The results are expected to deepen the existing knowledge about the diversity and sustainability of OA ecosystems.